Prospective evaluation through questionnaires of the emotional status of cancer patients in the waiting rooms of a department of oncology - Roberta Resega; Sheila Piva; Annalisa Bramati; Christian Lurati; Nicla La Verde; Marco Riva; Marina Chiara Garassino; Anna Moretti; Claudio Mencacci; Valter Torri; Gabriella Farina; Maria Chiara Dazzani (Journal of Health and Social Sciences)
Objective: The aim of this study is to better identify the prevailing emotions and feelings of cancer patients during their stay in waiting rooms in a department of oncology. Methods: In July 2014, patients in the waiting rooms of our Department of Oncology were asked to fill out dedicated questionnaires. Patients had to choose sentences that best described their feelings, thoughts and experiences; this part was differentiated according to the waiting rooms (Consultation Rooms versus Day Hospital). In another section, patients were asked to choose their prevailing primary emotions: joy, fear, sadness, anger, disgust or surprise. Results: Two hundred eighty questionnaires were considered valid for statistical analysis. Regarding feelings, all patients in the Day Hospital and Consultation Rooms stated that they feel anxious (48% and 53%, respectively). By differentiating patients according to the setting, patients in the Day Hospital answered that they will face chemotherapy, thinking that it will be useful to defeat the disease (56%), and patients in Consultation Rooms answered that time in the waiting rooms goes more slowly (65%). Regarding the prevailing emotions experienced by patients, sadness was the most selected, followed by fear and surprise. Conclusions: A prevalent emotional and cognitive state while waiting is anxiety, followed by positive thoughts. Patients presented anxiety and fear independently from the setting of care. We believe that each oncologist should be aware of the degrees of fear and sadness that patients experience during an oncological examination because these emotions can have an impact on communication and understanding.